Paronomasia and Rhymed Prose in the Treatise of Rights by Imam Ali ibn Al-Husayn (peace be upon them(A Phonetic and Semantic Study - Shakir Ghali , Lect .Dr. Shaimaa (Basra studies journal, 2026)
The research addresses the phonetic aspect in paronomasia (jinas) and rhymed prose (sajʿ), considering them among the most prominent manifestations of phonetic rhetoric. The study adopts an analytical method that combines traditional rhetorical description with modern phonetic analysis, aiming to reveal the effect of phonetic repetition, such as letter recurrence, phonemic harmony, pause, voicelessness, and vowel length, and to link these sound features to perception, rhetorical impact, and aesthetic effect. It also seeks to identify the most influential phonetic elements in generating the sensation of paronomasia or sajʿ, and to measure their relationship with meaning, eloquence, verbal rhythm, and memory retention. The study classifies the phonetic phenomena involved, such as: repetition of consonants (like sīn), vowel harmony, internal phonetic paronomasia, alternation of voiced and voiceless sounds, and repetition of light, voiceless consonants, which enhance smoothness and ease; whereas emphatic or guttural consonants add a heavier tone.